How Can Fiscal Policy Help Avert Currency Crises? - Kopits, George (IMF Working Papers; Working Paper ;, 2000)
An overview of crisis episodes in emerging-market economies with a pegged exchange rate regime in the 1990s suggests that sizable explicit or implicit government deficits, or market perceptions of lack of fiscal sustainability, render these economies vulnerable to currency crises under high capital mobility. It is argued in the paper that vulnerability to crisis can be mitigated by signaling a phased fiscal adjustment that involves credible implementation of key structural measures. In particular, fiscal policy rules, such as the ones being adopted in a number of emerging-market economies, constitute a potentially useful tool of crisis prevention.